2017
DOI: 10.1108/scm-07-2016-0227
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain management: an empirical investigation on the construction sector

Abstract: Supply Chain Management: an International Journal y C h a i n M a n a g e m e n t : a n I n t e r n a t i o n a l J o u 1 Green supply chain management: An empirical investigation on the construction sector Abstract Purpose: Curtailing the adverse environmental impacts of the construction sector is one the major challenges of the twenty-first century. However, despite the significance of this problem, the limited efforts so far to tackle the negative impacts associated with this particular sector have been lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
158
2
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(169 citation statements)
references
References 85 publications
(141 reference statements)
3
158
2
6
Order By: Relevance
“…As representative of the manufacturing industries, the construction industry needs materials from other industries to produce buildings or infrastructure. Therefore, the supply and demand model in the construction industry has significantly contributed to economic growth (Bohari, Skitmore, Xia, Teo, Zhang & Adham, 2015); this model is highly complex, diverse and fragmented, involving a multitude of stakeholders participating in dyadic relationships (Balasubramanian & Shukla, 2017a). For example, in a construction project like a building project, the number of organisations involved in the supply chain can run into the hundreds.…”
Section: Supply Chain Management In the Construction Industrymentioning
confidence: 99%
“…As representative of the manufacturing industries, the construction industry needs materials from other industries to produce buildings or infrastructure. Therefore, the supply and demand model in the construction industry has significantly contributed to economic growth (Bohari, Skitmore, Xia, Teo, Zhang & Adham, 2015); this model is highly complex, diverse and fragmented, involving a multitude of stakeholders participating in dyadic relationships (Balasubramanian & Shukla, 2017a). For example, in a construction project like a building project, the number of organisations involved in the supply chain can run into the hundreds.…”
Section: Supply Chain Management In the Construction Industrymentioning
confidence: 99%
“…Sizeable prior studies found that GSCM practices positively influence firm performance; environmental, economic, social or operational aspects (Balasubramanian & Shukla, 2017). Each of this aspect of performance is perceived as essential indicators of sustainability performance for organisations because the business environment nowadays is highly competitive and increasing demand from consumers regarding the environmental concern and the preference of eco-friendly products.…”
Section: Introductionmentioning
confidence: 99%
“…Successful Green SCM requires relationship management as part of the greater integration of business processes and systems along supply chains (Ahi & Searcy, 2013). The work of Balasubramanian and Shukla (2017a) pointed to the value in mapping between role and activities. Their research linked detailed green practices, drivers and barriers to four roles: developers, contractors, architects/consultants and suppliers.…”
Section: A Comprehensive Definition Of Green Scm In Constructionmentioning
confidence: 99%
“…Sertyesilisik (2016) proposed extending Porter's diamond framework of factors influencing competitiveness (Porter, 1998) to include requirements of future generations and broader 'sustainability conditions' Balasubramanian and Shukla (2017a) critiqued earlier theoretical frameworks of Seuring and Müller (2008a, b) and Carter and Rogers (2008) as not comprehensive and no longer up-to-date. They went on to offer the only new theoretical framework proposed for Green SCM in the papers reviewed (Balasubramanian, 2014;Balasubramanian and Shukla 2017a). Deriving first a quadrantbased categorisation of enablers of Green SCM, based on an extensive review of the Green SCM literature (Balasubramanian, 2014), Balasubramanian and Shukla (2017a) proposed and tested a nine-construct structural model, in which they demonstrated the relationship between internal and external drivers and barriers to core and facilitating green practices, and the relationship between core and facilitating green practices and environmental, economic and organisational performance.…”
Section: Theoretical Framingmentioning
confidence: 99%
See 1 more Smart Citation